Design of the shuttle-type picking and storage device for cherry fruit - Meihua Zhang; Hui Wu; Tinyong Cai; Wen Shi; Xingfu Xi; Yang Xiao (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
A shuttle-type cherry fruit picking and storage device is designed for cherry fruits to quickly assist manual picking. In this paper, the structure, parameters and motion transformation of this picking and storage device are introduced in detail. It has been proved to pick cherry fruits quickly and efficiently by experiments.